Critical Review on Waqf Experiences: Lessons from Muslim and Non-Muslim - Kamarubahrin, Aimu Fadzirul; Ahmed Ayedh, Abdullah Mohammed (IQTISHADIA, 2018)
The purpose of this paper is to critically assess current practices in waqf institution based on Middle East, Asia and some selected non-Muslim countries experience. Muslims countries have their own ways of managing waqf. Some ways are similar to one another and some are different. The methodology used in this study is in depth review analysis of the literature of waqf practices in various countries. The paper could conclude that differences of waqf institution based on legal factors, historic of establishment and current implementation. The paper identifies, that the objective establishment of Waqf institution is benefit to the society and development of the country. This paper is based on critical analysis review of the waqf experiences literature review in selected countries. Future research might integrate this review with empirical methodology. There is a limit number of countries waqf experiences have been included in this study, future research might include more experiences. In term of the implications of findings, it hopes that the findings give more comprehensive and cross countries picture of waqf experience and practice. Which is, it will assist the related waqf regulators in the evaluation process of waqf management practices and determine best practice as well set up a benchmark waqf management practices.Keywords: